The Influence of Online Cash Loan Service, Collection Ethics, and Service Integrity towards the Emotional Condition of User - Kurniawati, Yuli; Kusmayati, Nindya Kartika (LPPM of NAROTAMA UNIVERSITY, 2023)
Peer to peer lending financial tech apps are widely available on the internet by 2023. The number of app users is also significantly growing, especially after the epidemic began in late 2019. It is transforming the micro-economy today as new problems and hazards emerge. This study attempts to uncover the truth about the usage of peer-to-peer lending (P2PL), specifically their speedy loan service, as one of the independent factors to be examined, along with other variables such as collection ethics and service integrity, and their influence on the user's emotional condition. As of March 2023, the Financial Service Authority (OJK) announced that at least 23 P2PL enterprises were in TWP90 (non-performing loan) and 85 unlawful online cash loan services. This leads to the belief that many users have fled from responsibility due to improper collection methods, and the pressure felt by the user is one of the reasons why the return of the lending is considered a troublesome scenario. According to this study, online cash loan service, collection ethics, and service integrity all have an impact on the emotional state of the user.